Analysis of Marketing Strategies to Increase Competitiveness in Micro, Small and Medium Enterprises (MSMEs) Shoe Industry Ortins Namaste Art Kediri Regency - Bisri, Rohmat Khasan Bisri (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Purpose of the study:  The purpose  of this study is to analyze Marketing Strategy as an effort to increase competitiveness in micro, small and medium enterprises (MSMEs) of the Ortins Namaste Art shoe industry, Kediri Regency. Design / Method / Approach: This study uses a qualitative approach, where I obtained information through conservation activities in the place of business and interviews with 4 informants, namely owners, and employees, as well as 2 consumers from the ortins namaste art shoe industry. Research Findings: The result of this study is that MSMEs Ortins Namaste Art has implemented a 4P marketing mix strategy, where in terms of hanmade products that can be reques according to the wishes of MSME consumers this MSME also prioritizes quality both from materials and workmanship, and products can be servive back to craftsmen. In terms of price, it is quite expensive, but balanced with what consumers get, namely quality and durable products. And in terms of place, there is a weakness because it is in an alley and without an identity signpost, but the MSME Ortins Namaste Art has registered its location on google maps. And for promotion, it is still not implementing digital technology optimally, but these MSMEs work with sales sales to market their products. In addition, MSMEs Ortins Namaste Art strives to make innovations by always following existing trends, providing maximum service to consumers with an offline messaging system at the place of craftsmen and accompanied in choosing a model, this is intended so that the choice of consumers is really the best and quality. So that makes these MSMEs have superior value than other competitors. And the sales system only serves the location of craftsmen and is assisted by sales to offer their products to consumers. With these various advantages, there are still some aspects that are lacking that make the strategy in increasing the competitiveness of MSMEs Ortins Namaste Art Kediri Regency has not been maximized. Theoretical contribution / Originality: This research is expected to be able to increase information in the field of marketing strategies, especially for shoe craftsman MSMEs. And this research is an additional insight into the treasures of Economics in the field of marketing in increasing competitiveness. Implications of Practitionel / Policy: For MSME Owners This research is expected to be able to provide input in the form of advice and information to business owners regarding the competitive strategies carried out by these MSMEs. For Readers, this research is expected to be an additional reference for those who are interested in issues related to Competitive Strategies used by MSMEs. And for the local government, this research is expected to be an input or solution to develop MSME competitive strategy policies and the government always supports the sustainability of MSMEs, especially in the shoe industry in Kediri Regency Limitations of this study: The limitation of this study is the lack of detailed and complete data information because business owners only do simple recording.